Retinal Detachment Following Vaccination against COVID-19: A Narrative Literature Review - Markov, Gueorgui; Yani Zdravkov; Oscar, Alexander (Sriwijaya Journal of Ophthalmology, 2023)
Retinal detachment (RD) refers to the anatomical separation of the neurosensory retina from the Retinal pigment epithelium, which, if untreated, ultimately leads to a loss of visual function and blindness. Three main types are recognised based on the pathogenesis: rhegmatogenous, associated with retinal tears/holes; tractional, where there is pulling on the retina from preretinal and/or vitreal fibrotic changes; and exudative or serous, in which the subretinal fluid is due to transudation, exudation, or impaired outer blood-retina barrier. The infection with SARS-CoV-2 has not been directly associated with any type of RD, except in cases of secondary infections or autoimmune conditions. Serous retinal detachment has very rarely been observed following the application of various vaccines against COVID-19, but only in the setting of central serous chorioretinopathy and uveitis. The single case of purported rhegmatogenous detachment has a highly improbable connection with the vaccination. All in all, the described complications have been extremely uncommon, more frequently treatable or self-resolving, and should not discourage COVID-19 vaccination.